2022
DOI: 10.7181/acfs.2022.00850
|View full text |Cite
|
Sign up to set email alerts
|

Late reconstruction of post-traumatic enophthalmos and hypoglobus using three-dimensional implants: a case series

Abstract: Post-traumatic enophthalmos and hypoglobus are common sequelae of facial bone fractures, even after reduction surgery. They are associated with functional and esthetic issues, which may lower the quality of life. These deformities frequently present late, and adequate correction is difficult. We report three cases of late inferior orbital rim reconstructions with three-dimensional printed implants to help resolve these problems. The average duration between the traumatic event and surgery was 3 years and 4 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Current investigations into 3D printing technology explore its viability for crafting personalized orbital implants, with a significant body of research focusing on utilizing 3D models for implant customization [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] and for the creation of directly printed implants [ 45 , 46 , 47 , 48 , 49 , 50 ]. Chai et al (2021) demonstrated the efficacy of using patient-specific 3D-printed models as templates for intraoperative adjustments to implants, noting a marked decrease in both surgery duration and related complications [ 32 ].…”
Section: Applications Of 3d Printing In Oculoplastic and Orbital Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…Current investigations into 3D printing technology explore its viability for crafting personalized orbital implants, with a significant body of research focusing on utilizing 3D models for implant customization [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] and for the creation of directly printed implants [ 45 , 46 , 47 , 48 , 49 , 50 ]. Chai et al (2021) demonstrated the efficacy of using patient-specific 3D-printed models as templates for intraoperative adjustments to implants, noting a marked decrease in both surgery duration and related complications [ 32 ].…”
Section: Applications Of 3d Printing In Oculoplastic and Orbital Surgerymentioning
confidence: 99%
“…In summary, 3D printing provides several benefits in terms of accuracy and surgical outcomes ( Table 2 ), with most orbital implant guides made of titanium [ 35 , 36 , 37 , 38 , 39 ] and direct models made of polycaprolactone [ 45 , 46 , 47 ]. Nonetheless, several gaps remain.…”
Section: Applications Of 3d Printing In Oculoplastic and Orbital Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…This method leverages the mirroring of an unaffected orbit's anatomy over the damaged one to generate a preformed mesh. Transitioning from these conceptual frameworks, contemporary research has delved into the practicalities of personalized orbital implants, predominantly focusing on the role of 3D models for implant shaping and direct 3D-printed implants [35][36][37][38][39][40]. Chai et al (2021) used 3D-printed models of patient fractures as templates in intraoperative implant trimming [41], demonstrating a significant reduction in surgical time and complications.…”
Section: Metalsmentioning
confidence: 99%
“…Advanced imaging techniques and three-dimensional analyses of scans, together with virtual surgical planning for subtotal excision or complete excision of the lesion and reconstruction with autologous tissue or implants made by computer-aided manufacturing and patient-specific design, should be regarded as the standard of care in surgery for FD of the craniofacial skeleton [ 38 , 39 ]. Simple curettage is not recommended as a primary option, as it is ineffective and may increase the risk of complications [ 40 – 42 ].…”
Section: Managementmentioning
confidence: 99%